Epistemologia das sanções processuais: uma análise com enfoque nas astreintes e seu impacto na concretização de direitos - Aloisio, Anderson Bellini (Universidade do Vale do Rio dos Sinos, 2015)
Through a horizontal approach crossing two different theoretical matrixes, this work has the objective of showing the possibility of existing purely procedural sanctions, as well as their appropriateness to the “process” model in line with a democratic State governed by the rule of Law, according to constitutional values. In order to achieve this we have made a study on theories regarding human behavior to obtain information on how the sanctions may have influence on the decision process and obtain the desired behavior by citizens (obedience of legal precepts). After this we have re-analyzed the classic theories on the process in order to reassure its autonomy and also demonstrating that there is reminiscence of ties with the substantive rights that still harness the process as a mere instrument or a mere technique for attainment of the substantive rights already established by Law. After restating – or proposing – the definitive and ultimate separation of the substantive rights/process/procedure, we have concluded that the process turns to be seen as a space for development of the solution for the case, space which has to include strong ethical obligations and behavioral duties imposed to the litigants. The fulfillment of these duties is made independently of the duties imposed by the substantive rights. They are procedural rules – autonomous – which “per se” are to be fulfilled and as such they need sanctions to assure the corresponding fulfillment: the procedural sanctions. Finally, as we strongly believe that the Law should never disregard its operational range, in the last chapter of this work we have applied the theoretical concepts mentioned before. For this purpose we have narrowed down to legislation details in order to demonstrate, in the practice, how the theoretical postulates mentioned before operate – or should operate. In order to demonstrate such application, we have focused in demonstrating how the theoretical postulates would act in the application of astreintes. This choice was made because it is the most difficult procedural sanction to be studied due to the very strong informative elements deriving from the substantive rights. Therefore, our choice for astreintes was made precisely for considering the difficulties in treating it as an exclusive procedural sanction, being then easy to pass the concepts proposed here to other procedural sanctions, which are not under the same theoretical complexity as the astreintes. This work is part of the Research Line n. 1, of the Universidade do Vale do Rio dos Sinos - UNISINOS, namely, Hermeneutics, Constitution and Implementation of Rights.
Keywords: Astreintes; Sanção; Comportamento humano; Direito material; Processo; Autonomia; Sanctions; Human behavior; Substantive rights; Procedure law; ACCNPQ::Ciências Sociais Aplicadas::Direito